Digital Cognitive‐Motor Occupational Training with QEEG Monitoring in Schizophrenia Rehabilitation: An Exploratory Neurofunctional Study. - Khemthong, Supalak; Rueankam, Maliwan; Chatthong, Winai; Hilton, Claudia (Occupational Therapy International, 2026)
Introduction: Current occupational therapy assessments for schizophrenia rely primarily on behavioral observation, with limited access to objective neurofunctional indicators of cognitive–motor engagement. Digital tools combined with neurophysiological monitoring offer new opportunities to address this gap. This study examined a digital cognitive‐motor occupational training application paired with quantitative electroencephalography (QEEG) to explore neurofunctional engagement during task performance. Methods: Thirty individuals with schizophrenia completed structured occupational tasks under two conditions: with and without QEEG‐based Brain Mapping Performance (BMP). Task engagement was characterized using participant‐prioritized daily activities grouped into dopaminergic, serotonergic, oxytocinergic, and endorphin‐related behavioral domains, conceptualized as theoretical behavioral associations rather than direct neurochemical measures. QEEG indices included theta relative power, beta relative power, and theta/beta ratio recorded from six frontal and temporal scalp sites. Results: Theta relative power was higher at frontal and central sites (Fz and Cz) during BMP‐monitored conditions, reflecting executive and motor planning demands. Beta relative power varied across memory‐ and emotion‐related task phases, indicating task‐dependent modulation of cognitive effort. Engagement Intensity Scores were consistently higher in the unmonitored condition, while BMP monitoring was associated with longer task completion times and increased neurofunctional engagement. Conclusion: QEEG‐guided occupational task performance reveals distinct, task‐dependent neurofunctional patterns in schizophrenia rehabilitation. The integration of digital task‐based assessment with neurophysiological monitoring provides exploratory neurofunctional indicators that may support individualized, functionally informed occupational therapy interventions.